2013
DOI: 10.1093/bioinformatics/btt196
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating key position and amino acid residue features to identify general and species-specific Ubiquitin conjugation sites

Abstract: Motivation: Systematic dissection of the ubiquitylation proteome is emerging as an appealing but challenging research topic because of the significant roles ubiquitylation play not only in protein degradation but also in many other cellular functions. High-throughput experimental studies using mass spectrometry have identified many ubiquitylation sites, primarily from eukaryotes. However, the vast majority of ubiquitylation sites remain undiscovered, even in well-studied systems. Because mass spectrometry-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 31 publications
1
86
1
Order By: Relevance
“…Phosphosite plus supports this prediction with six different manuscripts which predicted the K333 site using proteomic discovery-mode mass spectrometry, thus strengthening the likelihood of a true ubiquitination site [41, 42]. In parallel, we used three additional bioinformatics tools (Ubiprober, Ubpred, BDM-PUB) and identified 13 candidate ubiquitination sites, including the K333 site previously predicted by discovery-mode mass spectrometry (Table 1) [43–45]. By looking at the position of each predicted site, we found that K185 and K188 are located within the SAC domain while K305, K325, K329 and K333 are located within the leucine zipper domain (Table 1) (Figure 4C).…”
Section: Resultsmentioning
confidence: 56%
“…Phosphosite plus supports this prediction with six different manuscripts which predicted the K333 site using proteomic discovery-mode mass spectrometry, thus strengthening the likelihood of a true ubiquitination site [41, 42]. In parallel, we used three additional bioinformatics tools (Ubiprober, Ubpred, BDM-PUB) and identified 13 candidate ubiquitination sites, including the K333 site previously predicted by discovery-mode mass spectrometry (Table 1) [43–45]. By looking at the position of each predicted site, we found that K185 and K188 are located within the SAC domain while K305, K325, K329 and K333 are located within the leucine zipper domain (Table 1) (Figure 4C).…”
Section: Resultsmentioning
confidence: 56%
“…On the basis of this observation UbPred was developed [262] (Table 1): a ubiquitylation site predictor based on a support vector machine algorithm (SVM), which allows studying the correlation between ubiquitylation and protein half-life. In order to overcome the lack of accuracy and training data deficiency, UbiProber [263] and iUbiq [264] were designed (Table 1). UbiProber predicts both general and species-specific ubiquitylation sites using large-scale experimental data as training set, while iUbiq is based on evolutionary information incorporated into the general form of pseudo-amino acid composition.…”
Section: Small Proteins' Modificationsmentioning
confidence: 99%
“…For example, in 2013, our laboratory developed a species-specific ubiquitin conjugation sites predictor and the results of cross-species predictions indicated that species-specific prediction can effectively promote the prediction performance of ubiquitin sites. 41 Another recent study presented a novel approach to predict species-specific lysine acetylation sites across six different species and their results justified the necessity and importance of developing species-specific models to improve the prediction of lysine acetylation sites. 76 While due to the limited data available before, the regulation mechanism of methylation among different species were not discussed in the field of methylation sites prediction.…”
Section: Future Perspectivesmentioning
confidence: 95%